Nano- TiO2/Nd Deposited on -Fe2O3 as a Magnetically Separable Photocatalyst - H. Ghasemi Mobtaker; S.J. Ahmadi; P. Ashtari (Journal of Sciences, Islamic Republic of Iran)
TiO2/Magnetit and TiO2/Nd/Magnetit were prepared and used for photocatalytic decomposition of the methylorange as a pollutant. TiO2 and TiO2/Nd were prepared by sol gel method and were characterized using XRD, FT IR and TEM. The prepared catalysts were deposited on magnetite surface to have a catalyst with magnetite core. So the catalyst can be separated easily from the waste solution by a magnet. Comparing the photocatalytic activity of TiO2/Magnetit and TiO2/Nd/Magnetit showed that doping the TiO2 by Nd increases the catalytic activity. Acidity of the waste has also promising effect on catalytic activity and the time needed for methylorange decomposition was decreased in low pHs. Complete decomposition of the methylorange was confirmed by LC MS.